Physicochemical properties of starch of four varieties of native potatoes - Mojo-Quisani, Antonieta; Licona-Pacco, Katiuska; Choque-Quispe, David; Calla-Florez, Miriam; Ligarda-Samanez, Carlos A.; Mamani-Condori, Raúl; Florez-Huaracha, Karin; Huamaní-Melendez, Víctor J. [UNESP] (Elsevier, 2024)
The limited industrial use of indigenous varieties of native potatoes has caused a decrease in its cultivation, restricting it to the self-consumption of the Andean population. The present study analyzed the physicochemical, thermal, and structural properties of the starches extracted from four of these varieties Aq'hu Pukucho, Yurakk Kkachun Wakkachi, Yurac Anca, and Huarmi Mallco, as a potential source of be used in industries such as food, pharmaceutical and, bioplastics. The percentage yield in wet extraction ranged between 14.53 and 20.26 %. The luminosity L* and whiteness index (WI) values were observed in ranges of 90.75–92.71 and 90.05–91.50, respectively. The Finding revealed various techno-functional properties, since the level of amylose varied between 36.29 and 43.97 %, an average zeta potential of −22 mV, and a maximum viscosity between 19,450–14,583 cP. The starches showed consistent thermal behavior since the TGA curves showed three stages with gelatinization temperatures that ranged between 54.9 and 59.75 °C, an enthalpy of 3.60–6.62 J/g, and various shapes of particles such as circular, elliptical, and oval. In conclusion, the relationships between variables such as water absorption index, swelling power, viscosity, crystallinity, enthalpy, and gelatinization temperature reveal different characteristics of each type of starch, which can influence its use.
Keywords: Amylose/amylopectin ratio; Color; Crystallization; Functional groups; Gelatinization; Morphology analysis; Swelling power